Pengaruh Lingkungan Sosial, Modal Usaha, Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha pada Masyarakat Desa Ayula Timur - Sri Asmi Hatim; Melizubaida Mahmud; Cristian Polamolo; Radia Hafid; Imam Prawiranegara Gani (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to determine the influence of social environment, business capital, and entrepreneurial knowledge on entrepreneurial interest in the community of Ayula Timur Village, Bone Bolango Regency, Gorontalo Province. This research employs a quantitative approach using a survey research method. The primary data used were collected through a questionnaire distributed to the residents of Ayula Timur Village. The sample comprises 64 respondents: farmers, plantation workers, livestock breeders, civil servants, entrepreneurs, and laborers. The data analysis technique employs multiple linear regression, assisted by the SPSS program. The results indicate that simultaneously, the variables of social environment, business capital, and entrepreneurial knowledge significantly influence entrepreneurial interest, with a significance value of 0.000. Partial testing results show that social environment, business capital, and entrepreneurial knowledge each positively influence entrepreneurial interest. The coefficient of determination (R-square) is 0.373 or 37.3%, meaning that the three independent variables collectively influence the dependent variable (entrepreneurial interest). In contrast, other factors outside the studied model influence the remaining 62.7%.